The Relationship between Soft-Tissue Balance and Intraoperative Kinematics of Guided Motion Total Knee Arthroplasty - Inui, Hiroshi; Taketomi, Shuji; Yamagami, Ryota; Shirakawa, Nobuyuki; Kawaguchi, Kouhei; Tanaka, Sakae (The Journal of Knee Surgery, 2019)
A new design of the so-called “guided-motion” total knee arthroplasty (TKA) is expected to produce normal-like kinematics. The implant behaves strictly as a mechanically constraint-guided motion system. However, no previous reports have demonstrated the most appropriate surgical technique or soft-tissue balance that would reproduce ideal kinematics. The purpose of this study was to clarify the relationship between soft-tissue balance and the intraoperative kinematics of guided-motion TKA. In this study, intraoperative kinematics of 95 patients whose TKA was performed with a guided-motion prosthesis (Journey II BCS Smith and Nephew) were measured using the computed tomography (CT)-free navigation system. All procedures were performed via the same soft-tissue balancing technique, which focused on the medial compartment because guided-motion TKA must acquire medial stability to induce medial pivot motion. We measured the extension and flexion osteotomy gaps using a force-controlled compartment-specific ligament tensioner with a distraction force of 80 N for each compartment and divided patients into three groups based on the relationship between extension and flexion joint osteotomy gaps of the medial compartment: group1– loose flexion gap, group 2–equal joint gap, and group 3–tight flexion gap. We compared the preoperative demographic characteristics, implant alignment, and intraoperative kinematics among the three groups. There was no difference between the preoperative demographic characteristics and postoperative implant alignment in the three groups. The relative tibial internal rotational angles in groups 1 and 2 were significantly larger than that in group 3 at 60°, 90°, and maximum flexion (p < 0.05). The appropriate soft-tissue balance of the medial compartment for guided-motion TKA was an equal joint osteotomy gap or a larger flexion than extension gap. A tight flexion gap should be avoided.
Keywords: total knee arthroplasty; guided-motion; soft-tissue balance; medial gap technique; intraoperative kinematics